Adverse Events of Exchange Transfusion in Neonatal Hyperbilirubinemia - Chitlangia, M; Shah, GS; Poudel, P; Mishra, OP (Journal of Nepal Paediatric Society, 2014)
Introduction: Jaundice is an important problem during neonatal period. When total serum bilirubin (TSB) level exceeds a critical limit, it crosses the blood brain barrier and results into bilirubin encephalopathy. The main aim of therapy for neonatal hyperbilirubinemia is prevention of bilirubin encephalopathy by phototherapy and/or exchange transfusion. The aims of this study were to evaluate the efficacy of exchange transfusion (ET) and observe the adverse events during and following three days of ET in neonates with hyperbilirubinemia. Materials and Method: Hospital based cross-sectional descriptive study. All neonates admitted to neonatal intensive care unit and /or paediatric wards of a tertiary- care centre between September 2010 to March 2012, requiring ET were enrolled. Results: A total of 139 ETs were performed in 120 neonates. The common causes were ABO incompatibility (30.8%), prematurity (30.8%), idiopathic (27.5%), Rh isoimmunization (6.7%) and cephalhematoma (4.2%). Mean pre- ET total serum bilirubin (TSB) was 24.2 mg% dL. There was 58% reduction in TSB in post ET and 31% net reduction in 6 hr post ET. Term and preterm neonates showed equal percentage of TSB reduction. Respiratory distress (10.8%) and bradycardia (6.7%) were the common adverse events during, and hypocalcemia (98.3%) and thrombocytopenia (34.2%) in 3 days following ET. The sick neonates had significantly higher incidence of thrombocytopenia (p= 0.031), respiratory distress (p=0.009), apnea (p<0.001) and cardiorespiratory arrest (p<0.001). Overall mortality was 4.2%, and non-survivors were mostly low birth weight, born outside the present hospital and had higher incidence of adverse events. Conclusion: Exchange transfusion is an effective intervention in reducing the serum bilirubin level. However, these neonates require monitoring of ionised calcium and thrombocytopenia. Sick neonates had higher incidence of adverse events than healthy and close clinical monitoring is needed to improve the outcome. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9030 J Nepal Paediatr Soc 2014;34(1):7-13